Change management excellence : putting NLP to work in the 21st century - Roberts, Martin (Wales : Crown House, 1999)
This book is about: Introducing NLP and modern developments in change management; Developing excellence in communication and understanding how other people tick; Developing excellence in change management; ...
Keywords: Management; Organization; Reengineering; Neurolinguistic programming; Organizational change -- Management; Reengineering (Management); Neurolinguistic programming